The Effect Of Debt Structure And Family Ownership On Firm Performance - Ijudin,; Azis, Azolla Degita; Yudhawati, Diah (Jurnal HARMONI: Jurnal Akuntansi dan Keuangan, 2023)
The purpose of this quantitative research is to find out how debt structure and family ownership affect the performance of manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2021. With a population of 120 out of 40 samples of manufacturing companies listed on the Indonesia Stock Exchange were selected through a purposive technique sampling. This study uses secondary data and is analyzed using multiple linear regression.The results of this study indicate that the debt structure has a significant negative effect on company performance as measured using the Debt to Asset Ratio (DAR). This is because the higher the use of debt, the greater the risk that will be borne by the company, so that it can reduce the company's financial performance. Meanwhile, ownership structure has no significant effect on firm performance as measured by the dummy variable. This is due to the lack of family control over the company. According to this study, family firms tend to have positive control over their business and limit their use of debt. This is because the family tends to have positive control over the company and lower debt, which can improve company performance.